S
Shai Rosenfeld
syntax question:
i have a 'case' expression:
case number
when 1: var = 'one'
when 2: var = 'two'
when 3: var = 'three'
else
var = 'else'
end
but instead of assigning the 'var' variable for each 'when', what is the
way to write the case statement, so i can assign 'var' at the end?
(something like
case number
when 1: 'one'
when 2: 'two'
when 3: 'three'
else
'else'
end >> var
[humm, a more elegant way]
)
i have a 'case' expression:
case number
when 1: var = 'one'
when 2: var = 'two'
when 3: var = 'three'
else
var = 'else'
end
but instead of assigning the 'var' variable for each 'when', what is the
way to write the case statement, so i can assign 'var' at the end?
(something like
case number
when 1: 'one'
when 2: 'two'
when 3: 'three'
else
'else'
end >> var
[humm, a more elegant way]
)